2014
DOI: 10.1063/1.4890239
|View full text |Cite
|
Sign up to set email alerts
|

Tuning magnetotransport in PdPt/Y3Fe5O12: Effects of magnetic proximity and spin-orbit coupling

Abstract: Anisotropic magnetoresistance (AMR) ratio and anomalous Hall conductivity (AHC) in PdPt/Y 3 Fe 5 O 12 (YIG) system are tuned significantly by spin orbital coupling strength ξ through varying the Pt concentration. For both Pt/YIG and Pd/YIG, the maximal AMR ratio is located at temperatures for the maximal susceptibility of paramagnetic Pt and Pd metals. The AHC and ordinary Hall effect both change the sign with temperature for Pt-rich system and vice versa for Pd-rich system. The present results ambiguously … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
5
23
2
Order By: Relevance
“…For the as-deposited multilayer, ρ AH increases with the increase of measuring temperature. It is noteworthy that ρ AH decreases nonlinearly with increasing measuring temperature for all annealed multilayers, which also differs from reports for Co 2 MnSi monolayer and other multilayer systems such as CoFeB/Pt and Fe/Au [22,24,31], while it is similar to the tendency of Pd/YIG film [46]. For the Pd/YIG system, it is suggested that the magnetic proximity plays an important role in contributing to AHE, which could lead to the decreased ρ AH with increasing measuring temperature [46].…”
Section: Anomalous Hall Effect (Ahe)contrasting
confidence: 98%
“…For the as-deposited multilayer, ρ AH increases with the increase of measuring temperature. It is noteworthy that ρ AH decreases nonlinearly with increasing measuring temperature for all annealed multilayers, which also differs from reports for Co 2 MnSi monolayer and other multilayer systems such as CoFeB/Pt and Fe/Au [22,24,31], while it is similar to the tendency of Pd/YIG film [46]. For the Pd/YIG system, it is suggested that the magnetic proximity plays an important role in contributing to AHE, which could lead to the decreased ρ AH with increasing measuring temperature [46].…”
Section: Anomalous Hall Effect (Ahe)contrasting
confidence: 98%
“…Smaller saturation magnetization leads to weaker exchange interaction and thus lower Ton,MPE. Negative [6,28] Negative (this work) Table I…”
Section: Figures and Captionsmentioning
confidence: 82%
“…With the information from the AHE, we can extract the exchange coupling configuration in arbitrary HM/magnetic insulator (MI) bilayers. For instance, Zhou et al[6] and Amamou et al[29] observed the AHE signs due to MPE are negative and positive for the Pd/YIG and Pt/CoFe2O4 (CoFe2O4 is a MI), respectively, so that we can predict parallel exchange coupling for both Pd/YIG and Pt/CoFe2O4 by usingTable I. We also summarize results of the exchange coupling configurations in HM/magnet bilayers inTable II[6,26,27,[29][30][31],…”
mentioning
confidence: 88%
“…The spin Hall magnetoresistance (SMR) and the spin Seebeck effect are two interesting observations when Pt is attached to a ferromagnetic insulator Y 3 Fe 5 O 12 (YIG), both of which are related to a pure spin current flowing along the direction normal to the YIG/Pt interface [5][6][7][8][9]. Unfortunately, the possible existence of the magnetic proximity effect (MPE) at the YIG/Pt interface complicates the detection of the SMR signals [10][11][12][13][14][15][16]. Similarly, the MPE-induced FM ordering in the Pt film associated with the anomalous Nernst effect becomes an obstacle for the quantitative characterizations of the spin Seebeck effect, due to an induced spin polarized current parallel with the spin current [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%